The Use of Data Envelopment Analysis for Selection of Investment Objects - Rimkuvienė, Daiva (Ekonomika, 2004)
Due to limited resources the State support can be delivered only to part of the enterprises that apply for it. To increase the effectiveness of investment policy, support has to be provided for enterprises having not only good financial results, but also perspectives of effective work in future. Commonly, more attention is paid to analysis of financial results. However, financial indexes describe the enterprise’s position in the past and do not reflect its possibilities of development. The estimation of an enterprise’s future effectiveness requires accounting for not only its financial results, but also for the efforts of employees to improve their qualification, to use information technologies, to use rationally natural resources. Those who analyse the enterprise’s activity in different aspects encounter problems of the object’s intercomparison due to the variability of the indexes. Data Envelopment Analysis allows to put the objects into a line according to a lot of criteria expressed in various measures, and to choose a number of input and output indexes. The paper presents the aspects estimating the future of an enterprise, the results of enterprise activity effectiveness evaluation using the Data Envelopment Analysis method, and a discussion about the possibilities to use this method.